LEED practices, certification, and accreditation handbook - Kubba, Sam (Butterworth-Heinemann/Elsevier, 2010)
Adopted in the United States and a number of other countries, LEED? certification is the recognized standard for measuring building sustainability. Achieving LEED? personal certification or project certification is the best way to demonstrate that the project is truly "green." Written by an architect with over 30 years of international experience, this book provides architects, designers, building owners, and construction engineers with an easy to understand guide to the nuts and bolts of LEED? project and personal certification. Written in plain and easy to understand language, this?hands o.
Keywords: Sustainable buildings -- Design and construction -- Standards -- United States -- Examinations -- Study guides.; Leadership in Energy and Environmental Design Green Building Rating System -- Examinations -- Study guides.; elektronické knihy; electronic books